2021
DOI: 10.1007/s12020-021-02684-3
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone deiodinases response in brain of spontaneausly hypertensive rats after hypotensive effects induced by mandibular extension

Abstract: Purpose:The deiodinases activate or inactivate the thyroid hormones (TH) in virtually all tissues in both physiological and pathological conditions. The three deiodinases, DIO1, DIO2 and DIO3, have different catalytic functions and regulate TH tissue distribution. The aim of the present study was to evaluate the modulation of gene expression of the deiodinases and TH transporters and protein levels of DIO1 in parietal and frontal areas of cerebral cortex of spontaneously hypertensive rats (SHRs), after two suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In mice that experienced 3 hours of status epilepticus (SE) caused by pilocarpine, the mRNA expression of Dio2 increased rapidly in the hippocampus, amygdala, and prefrontal cortex; however, the targeted disruption of Dio2 in astrocytes of mice had effects on highly induced genes in the hippocampus associated with inflammation, apoptosis, and cell death, suggesting that Dio2 induction caused by SE accelerated the production of T3 in different areas of the CNS and modified the hippocampal gene expression profile, affecting the balance between adaptive and maladaptive mechanisms [ 64 ]. Moreover, Dio2 mRNA expression significantly increased in the frontal cortex of two mandibular extension-treated rats compared with sham-operated rats, indicating the major involvement of Dio2 in an attempt to restore more physiological conditions and correct T3 levels, associated with normotensive status in the brain [ 65 ]. A recent result also showed that mice lacking both monocarboxylate transporter 8 ( Mct8 ) and Dio2 presented peripheral and brain hypothyroidism; the severity of the brain hypothyroidism seemed permanent and varied across regions, with the striatum being a particularly affected area, and brain alterations were observed at the histological level compatible with TH deficiency and impaired motor skills [ 66 ].…”
Section: Physiological Functions Of Dio2mentioning
confidence: 99%
“…In mice that experienced 3 hours of status epilepticus (SE) caused by pilocarpine, the mRNA expression of Dio2 increased rapidly in the hippocampus, amygdala, and prefrontal cortex; however, the targeted disruption of Dio2 in astrocytes of mice had effects on highly induced genes in the hippocampus associated with inflammation, apoptosis, and cell death, suggesting that Dio2 induction caused by SE accelerated the production of T3 in different areas of the CNS and modified the hippocampal gene expression profile, affecting the balance between adaptive and maladaptive mechanisms [ 64 ]. Moreover, Dio2 mRNA expression significantly increased in the frontal cortex of two mandibular extension-treated rats compared with sham-operated rats, indicating the major involvement of Dio2 in an attempt to restore more physiological conditions and correct T3 levels, associated with normotensive status in the brain [ 65 ]. A recent result also showed that mice lacking both monocarboxylate transporter 8 ( Mct8 ) and Dio2 presented peripheral and brain hypothyroidism; the severity of the brain hypothyroidism seemed permanent and varied across regions, with the striatum being a particularly affected area, and brain alterations were observed at the histological level compatible with TH deficiency and impaired motor skills [ 66 ].…”
Section: Physiological Functions Of Dio2mentioning
confidence: 99%
“…3 ). Moreover, the same study showed higher DIO1 protein levels in the parietal (but not frontal) cortex of SHR brain after two mandibular extensions, raising interesting questions about the role of this enzyme in TH system homeostasis in hypertensive conditions, which await further investigations [ 56 ].…”
Section: Deiodinases and Th Signalingmentioning
confidence: 99%